Hubungan Hiperurisemia dengan Penurunan LFG pada Pasien Penyakit Ginjal Diabetes di RSCM Jakarta - Adna, Rury Maharani; Marbun, Maruhum Bonar Hasiholan; Rinaldi, Ikhwan; Yunir, Em; Koesnoe, Sukamto; Singh, Gurmeet; Sinto, Robert (Jurnal Penyakit Dalam Indonesia, 2025)
Introduction. Elevated serum uric acid levels are associated with the progression of kidney disease in patients with type 2 diabetes mellitus (DM), through mechanisms involving endothelial dysfunction, oxidative stress, and chronic inflammation. Research in Indonesia on the relationship between uric acid levels and the decline of glomerular filtration rate (GFR) in diabetic patients remains limited. This study aimed to determine the association between serum uric acid (SUA) levels and decline in glomerular filtration rate among patients with diabetes mellitus diagnosed with diabetic kidney disease at Cipto Mangunkusumo Hospital, Jakarta, over a one-year period. Methods. This retrospective cohort study analyzed medical records of 192 type 2 diabetes melitus patients attending the Endocrinology and or Kidney Hypertension Clinics at Cipto Mangunkusumo National General Hospital , Jakarta. Inclusion criteria were baseline glomerular filtration rate ≥60 mL/min/1.73 m², available baseline serum uric acid, and follow-up glomerular filtration rate after one year. Bivariate and multivariate analyses were performed, adjusting for confounders including age, sex, hypertension, body mass index (BMI), triglycerides, HDL, LDL, total cholesterol, HbA1c, fasting blood glucose, and albuminuria. Results. Hyperuricemia prevalence was 85.94%. Multivariate analysis revealed that elevated SUA levels (≥6 mg/dL in women, ≥7 mg/dL in men) were associated with a 13.5% higher risk of GFR decline compared to normal serum uric acid (RR 1.135; 95% CI 1.015–1.268) after adjustment. Higher Body mass index was protective against glomerular filtration rate decline, while lipid profile, HbA1c, and fasting blood glucose were not significantly associated with diabetic kidney disease progression. Conclusions. Hiperuricemia is an independent risk factor for diabetic kidney disease progression in type 2 diabetes mellitus. Regular monitoring and management of serum uric acid may be crucial in preventing kidney function decline in this population.